INNOVATIVE AND INCLUSIVE APPROACHES TO ADVANCING STEM EDUCATION THROUGH EMERGING TECHNOLOGIES AND PEDAGOGICAL STRATEGIES: A NARATIVE REVIEW - Zain, Norhayati Mohd (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This review paper explores innovative and inclusive approaches to enhancing STEM education by synthesizing recent literature (2022–2025) on emerging technologies and pedagogical strategies. Stem education faces persistent equity gaps, necessitating combined technological and inclusive innovations to foster engagement and accessibility among underrepresented groups. The review identifies major technological advancements, including artificial intelligence adaptive frameworks, immersive virtual and augmented reality environments, robotics integration, and Internet of Things-enabled multisensory learning. It further examines equity-focused pedagogies encompassing culturally responsive teaching, gender gap mitigation, assistive technologies for learners with disabilities, and community outreach to promote inclusion. The intersection of mental health support with STEM education emerging in recent studies, emphasizes holistic learner wellbeing. Synthesizing these themes reveals synergistic models combining technological innovation with diversity, equity, inclusion, and justice (DEIJ) frameworks, supporting Education 4.0 transformations. This comprehensive review underscores the critical role of integrating advanced technologies with inclusive pedagogies to advance STEM education equitably, offering directions for future research to address remaining gaps and optimize learner outcomes.